2016
DOI: 10.1101/048397
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Using Google Earth to improve management of threatened limestone karst ecosystems in Peninsular Malaysia

Abstract: 15Biodiversity conservation is now about prioritisation, especially in a world with limited 16 resources and so many habitats and species in need of protection. However, we cannot 17 prioritise effectively if historical and current information on a particular habitat or species 18 remains scattered. Several good platforms have been created to help users to find, use and 19 create biodiversity information. However, good platforms for sharing habitat information 20 for threatened ecosystems are still lacking. Li… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
17
0
2

Year Published

2017
2017
2024
2024

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 7 publications
(19 citation statements)
references
References 32 publications
0
17
0
2
Order By: Relevance
“…For limestone karst localities, we followed the standard format of code and name (e.g. PRK 18 Gunung Lanno) used in the limestone hill register by Liew et al (2016) . Place names in this paper contain Malay words, namely: Batu = rock; Bukit/Buket = hill; Gua = cave; Gunung/Gunong = mountain; Kota = large tower karsts or fortress; Kuala/Kwala = estuary or river confluence; Pulau = island; Sungai/Sungei = river; Tasik = lake; Wang = large doline or valley surrounded on all sides by tower karsts.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…For limestone karst localities, we followed the standard format of code and name (e.g. PRK 18 Gunung Lanno) used in the limestone hill register by Liew et al (2016) . Place names in this paper contain Malay words, namely: Batu = rock; Bukit/Buket = hill; Gua = cave; Gunung/Gunong = mountain; Kota = large tower karsts or fortress; Kuala/Kwala = estuary or river confluence; Pulau = island; Sungai/Sungei = river; Tasik = lake; Wang = large doline or valley surrounded on all sides by tower karsts.…”
Section: Methodsmentioning
confidence: 99%
“… Alycaeus altispirus is not included in the maps because no specific locality was given for the materials examined (see Discussion section under the species). Note the red areas are limestone karsts (derived from Liew et al 2016 ).…”
Section: Methodsmentioning
confidence: 99%
“…The State of Perak has the third largest number of limestone hills, but it has the largest number of operating quarries (Liew et al 2016). The majority of these hills can be found within the Kinta Valley, with some other hills scattered around the northern part of the Kinta Valley and Bintang Range (Figure 1).…”
Section: Introductionmentioning
confidence: 99%
“…This species is known from the summit of two isolated karst limestone hills in Relai Forest Reserve, Gua Musang District, Kelantan and Gua Tanggang, Merapoh, Pahang, about 40 km apart (Liew et al 2016). Together they have an area of occupancy of less than 10 km 2 (Figure 3).…”
Section: Taxonomymentioning
confidence: 99%
“…Kiew et al 2017 demonstrated that no single hill has more than a fraction of limestone flora and that 192 species are endangered being known from less than five localities limestone hills, for example Monophyllaea musangensis A. Weber (Weber 1998), Gymnostachyum kanthanense Kiew, Meiogyne kanthanensis Ummul-Nazrah & J.P.C.Tan and Vatica kanthanensis Saw (Tan et al 2014), Impatiens glaricola Kiew and Impatiens vinosa Kiew (Kiew 2016). Therefore, limestone hills are one of the most threatened vegetation types in Peninsular Malaysia and are recognised nationally as Environmentally Sensitive Areas because of their high biodiversity and vulnerability (73 of the 445 hills are the sites of active or former quarries, Liew et al 2016). In addition, many karsts are still incompletely known botanically meaning that new species await discovery.…”
Section: Introductionmentioning
confidence: 99%